2018
DOI: 10.1055/s-0044-102134
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Segmental Speeds as a Function of Maturation in Youth Baseball Pitchers

Abstract: The purpose of this study was to determine how stride length, segmental sequencing of the pelvis, trunk, humerus, and forearm velocities and accelerations, and the timing of these values change as youth mature. Thirteen youth baseball pitchers participated at three consecutive time points: visit 1 (10.7±1.3 years; 151.8±10.7 cm; 45.0±9.65 kg), visit 2 (11.5±1.6 years; 155.5±11.1 cm; 50.4±10.0 kg), and visit 3 (12.4±1.7 years; 161.5±11.7 cm; 56.4±10.8 kg). Participants executed three pitches for a strike to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…This tendency affected the ball contact, with the U8 exhibiting a narrower upper trunk-to-pelvis separation angle than the U10. Notably, the lower extremity and trunk provide a foundation for the kinetic chain [ 10 , 23 ] and contribute approximately 54% of the total force developed during a tennis serve—a rotational motion similar to baseball batting. In addition, when the trunk movement exerts its maximum power, it is predicted that the ball will be hit more strongly if the extra power to twist the trunk is still reserved during ball contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency affected the ball contact, with the U8 exhibiting a narrower upper trunk-to-pelvis separation angle than the U10. Notably, the lower extremity and trunk provide a foundation for the kinetic chain [ 10 , 23 ] and contribute approximately 54% of the total force developed during a tennis serve—a rotational motion similar to baseball batting. In addition, when the trunk movement exerts its maximum power, it is predicted that the ball will be hit more strongly if the extra power to twist the trunk is still reserved during ball contact.…”
Section: Discussionmentioning
confidence: 99%
“…Assaiante and Amblard [ 9 ] reported that little head-to-upper trunk separation occurs during rotational movements until approximately 6 or 7 years. However, young pitchers show poor pelvic and trunk rotation timing, resulting in these segments facing the target too early during the throwing motion [ 10 , 11 ]. Batting requires the simultaneous motion of both arms; therefore, it is easily affected by the turning motion.…”
Section: Introductionmentioning
confidence: 99%
“…This result provides preliminary support for the use of the closed kinetic chain upper extremity stability test as a clinical assessment of a pitcher's ability to efficiently transfer energy within the upper extremity during the pitch. pitching motion utilizing proximal stability for distal mobility would require less muscular torque from the shoulder because of efficient energy transfer from more proximal segments, potentially reducing the risk of injury [11][12][13]. However, the intersection of efficient energy flow and joint stability within the GH joint has not been examined.…”
Section: Introductionmentioning
confidence: 99%